Pemberdayaan Pengemudi Bus Lb.Bulus-Tasikmalaya untuk Promosi Pariwisata Jawa Barat - Ngarbingan, Hubertina Karolina; Suruyantari, Yulita; Akbara, Anisa Zahwa; Satyarini, Ni Wayan Marsha; Lanisy, Nihan Anindiyaputra; Mulyana, Andy (Gandhi: Jurnal Pengabdian Kepada Masyarakat, 2024)
West Java tourism has great potential to attract domestic and international tourists. Throughout 2022, 52.3 million domestic tourists will visit tourist attractions in West Java, while the number of foreign tourists will reach 146 thousand. The main attraction of West Java is its rich natural resources and traditional cultural heritage. The foundations of this culture are still felt strongly in the community, especially in their skills in making crafts and souvenirs, which are the main theme of this region. Therefore, bus drivers serving the route of Lb. Bulus-Tasikmalaya has great potential to promote West Java tourism. Interaction with many tourists from various regions and backgrounds, during a long journey that takes around 8-10 hours can be used as a golden opportunity to promote West Java tourism. One of them is by providing information about tourist destinations in West Java, such as natural, cultural, culinary, and historical tourist attractions. This PkM aims to empower Lb bus drivers. Bulus-Tasikmalaya to become an effective West Java tourism promotion agent. Data was collected through observation, interviews, and documentation. Observation results show that bus drivers have limited knowledge about West Java's tourism potential. Apart from that, bus drivers also do not have adequate tourism promotional materials. Based on the results of observations, it is recommended to empower bus drivers through training, providing tourism promotional materials, and providing incentives. By providing training, providing tourism promotion materials, and incentives, bus drivers experience increased knowledge and skills in promoting the tourism image of West Java, improve the quality of service and charity towards tourists, and increase tourist interest.